HEDGES IN INTERVIEW OF SUNDAY TELEVISION PROGRAM JULIA GILLARD - MILADIYAH, ZAKIYATUL; ARIYANTI, LISETYO (LANGUAGE HORIZON, 2018)
Abstract This study examines the use of hedges in politic field, especially in interview of Sunday television program that has focus in Julia Gillard?s Utterances. The purpose of this study is to find out and describe about the types of hedges expressions and how do hedges expressions serve a function in Julia Gillard?s responds in the interview by using theories of Francoise Salager-Meyer in Miller (1994) about the typology of hedges expressions, and the function of hedges expressions. The method that is used in this research is quantitative method which is focused in analyzing the use of hedges in an interview of Julia Gillard?s at Sunday program. The result shows that the types of hedges mostly used in the interview are modal auxiliary verbs, such as can, could, will, would, should and shouldnot. The other types of hedges belong to modal lexical verbs; adjectival, adverbial, and nominal modal phrase; approximators of degree, quantity, frequency, and time; introductory phrases; and if clause. In this research the compound hedges type does not be found. While the functions are minimize the threat to face; ways of being more precise in reporting result; and as a politeness strategy. It is also possible that in each of the functions contain some of hedges types.Keywords: Hedges, Forms of Hedges, Kind of hedges Used by Julia Gillard, Sunday ProgramAbstrakPenelitian ini meneliti hedges di bidang politik, terutama dalam wawancara program televisi hari Minggu yang berfokus pada ucapan Julia Gillard. Tujuan dari penelitian ini adalah untuk mengetahui dan menjelaskan tentang jenis-jenis hedges dan bagaimana fungsi hedges bekerja dalam respon Julia Gillard dalam wawancara dengan menggunakan teori-teori Francoise Salager-Meyer dalam Miller (1994) tentang tipologi hedges, dan fungsi hedges. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif yang difokuskan dalam menganalisis penggunaan hedges dalam wawancara dengan Julia Gillard di Sunday program. Hasil penelitian menunjukkan bahwa hedges yang paling banyak digunakan dalam wawancara adalah kata kerja modal tambahan, seperti can, could, will, would, should, danshould not. Hedges lainnya termasuk modal kata kerja leksikal; frase modal kata sifat, kata keterangan, dan nominal; perkiraan derajat, kuantitas, frekuensi, dan waktu; frasa pengantar; dan jika klausa. Dalam penelitian ini, tipe gabungan hedges tidak ditemukan. Sementara fungsi hedges dalam ucapan Julia Gillard adalah meminimalkan ancaman yang akan dihadapi; cara lebih tepat dalam melaporkan hasil; dan sebagai strategi kesopanan. Dalam hal ini, memungkinkan bahwa di masing-masing fungsi bisa terdiri dari beberapa jenis hedges.Kata kunci: Hedges, Bentuk Hedges, Jenis Hedges yang Digunakanoleh Julia Gillard, Program Minggu